Cleaner air would enhance India's annual solar energy production by 6–28 TWh. (1st May 2022) - Ghosh, Sushovan; Dey, Sagnik; Ganguly, Dilip; Baidya Roy, Somnath; Bali, Kunal
Abstract: India has set a target of 100 GW solar installation capacity by the year 2022. However, the loss of solar energy due to environmental factors like air pollution is not properly considered in renewable energy resource assessments. Here we show that India lost 29% of its utilizable global horizontal irradiance potential due to air pollution between 2001 and 2018. The average loss in output incurred by solar power systems with horizontal, fixed-tilt, single-axis, and dual-axis trackers due to air pollution is estimated to be 12%, 26%, 33%, and 41%, respectively, equivalent to a loss of 245–835 million USD annually. The successful implementation of the National Clean Air Program and the complete mitigation of household emissions through the supply of cleaner fuel for domestic use and rural electrification would allow India to generate a surplus of 6–16 TWh of electricity per year from the existing installed solar power capacity in 2018. This translates to an economic benefit of 325–845 million USD annually, which is equivalent to the implementation costs of these social programs. Mitigating air pollution would therefore accelerate India's progress towards achieving its solar energy target at a lesser installation capacity, avoiding additional expenditure for the expansion of the solar energy infrastructure.